MAINTENANCE ACTION ON COURSE POWER AMPLIFIER TRANSMITTER GLIDESLOPE SELEX 2110 - Atmaja, Brahmantya Adi; Yoga, Mochamad Faisal; Saragih, Sarrum Hadid Habib (Journal of Airport Engineering Technology (JAET), 2024)
The Instrument Landing System (ILS) equipment is one of the aviation navigation tools that provides aircraft with a 3° landing angle. The problem identified that the glideslope signal was out of tolerance. Pilots using the glideslope facility reported this out-of-tolerance signal. This study aimed to identify issues in signal transmission systems and give a solution. The research method was a descriptive analysis to determine the cause of the out-of-tolerance glideslope signal. The result found that the issue was that one of the power amplifiers of the glideslope transmitter was unable to process signals properly, resulting in suboptimal signal transmission power. The power amplifier was replaced to address this issue. This replacement was followed by adjusting the transmission parameters of the glideslope equipment. With the replacement of the power amplifier and the adjustments made to the transmission parameters, the glideslope signal returned to normal, as confirmed by the reports from pilots using the glideslope facility.